Palma forrageira na alimentação de bezerros mestiços leiteiros na fase de transição - Gomes, Rayane Nunes (2014)
This research have objective to evaluate the rumen development and performance of crossbred dairy calves in the transition phase from a liquid diet to a solid diet fed spineless cactus replacing of Tifton . 16 crossbred calves (Holstein x Zebu) were used in the phase of transition from liquid diet to a solid diet, with average initial weight of 50.04 + 6.3 kg. Calves were housed in individual hutches and mobile breastfed artificially with 4 liters of milk / day until 30 days. By completing 31 days began the trial period where the calves started to receive treatment. Treatments consisted of the replacement of Tifton 85 hay and also part of the concentrate by spineless cactus (Opuntia ficus indica , MILL), as follows: T1 (DPA): 70 % concentrate + 30 % hay Tifton , T2 (SPV) : 70 % concentrate + 15 % of Tifton hay + 15 % palm , T3 (STV) : 70 % concentrate + 30 % palm, T4 (SCV): 50 % concentrate + 17 % hay Tifton + 33 % palm. Diet consumption, body measurements, body and fecal scores, were performed weekly until 67 days of age, when these animals were slaughtered to evaluate the development of the upper digestive tract, rumen papillae, carcass and meat. Diet consumption, body weight and body measurements don’t showed significant difference (P>0,05) between treatments. The dry matter intake was not influenced by treatments and average 0,48 kg / d. The average observed in fecal scores during the experimental period shows that there was no incidence of diarrhea in animals. No differences between treatments (P>0,05) for the weight of the upper digestive tract and weight of each compartment when divided into the rumen - reticulum , omasum and abomasum were observed. The rumen papillae height (mm) of dairy crossbred calves fed diets with forage cactus replacing Tifton hay was influenced by diet. Treatment with total replacement of Tifton hay for forage cactus showed better development of rumen pupils, with an average of 4.48 mm. The use of cactus in calves fed influenced (P < 0.05) the thickness of the muscle layer rumen, the largest development observed with treatments containing palm. The ruminal epithelium and keratinized portion of the rumen were influenced (P< 0.05) among treatments, and further development was observed for the standard diet containing Tifton hay as forage source. There was no significant difference (P<0.05) in the carcass characteristics. Treatments did not affect the pH of the meat and shear force (FC), since the weight loss by cooking (PPC) was influenced (P< 0,05) among treatments . Parameters related to meat color showed no significant differences between treatments (P>0.05). The use of cactus pear replacing Tifton hay as roughage in the diet of crossbred calves in the transition phase from a liquid diet to a solid diet is indicated, assisting in early weaning without affecting growth, rumen development and carcass characteristics and meat from these animals.